The Role of Acetaminophen Use in Acute Kidney Injury Prevention in Cardiac Surgery: A Systematic Review and Meta-Analysis - Luis E. Ciconini; Victor Perim; Theodoro Beck; Mauren F. Carbonar; Mazpa M. Ejikem; Ahmed Zaky; Javier Neyra; Andre F. Gosling (Annals of Cardiac Anaesthesia)
Acute kidney injury (AKI) is a common complication following cardiac surgery, often leading to increased morbidity and mortality. Despite its prevalence, the role of acetaminophen in preventing AKI after cardiac surgery remains uncertain. This meta-analysis sought to clarify whether perioperative administration of acetaminophen could reduce the risk of postoperative AKI in adult patients undergoing cardiac procedures. To address this question, a systematic review and meta-analysis were performed by searching the MEDLINE, Cochrane, and Embase databases. Studies comparing the effects of perioperative acetaminophen to those of no acetaminophen in adult cardiac surgery patients were evaluated, with risk of bias assessed for each study. Sensitivity analyses were also conducted to strengthen the reliability of the findings. In total, 13 studies, including nine randomized controlled trials and four observational studies, involving 11,583 patients, were analyzed. The results showed that acetaminophen administration was associated with a lower incidence of AKI [OR 0.62 (95% CI 0.40–0.97), P = 0.04]. Additionally, acetaminophen use was linked to reduced in-hospital mortality, delirium rates, and shorter ICU stays, though it had no significant effect on overall hospital length of stay. These findings suggest that perioperative acetaminophen administration may play a protective role in reducing both AKI incidence and in-hospital mortality in patients undergoing cardiac surgery. Until large multicenter randomized controlled trials confirm these results, acetaminophen may still be considered as a preventive measure for patients both before cardiopulmonary bypass initiation and in the postoperative period.